2006
DOI: 10.1128/jvi.00068-06
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Substitutions Restore Normal Core Assembly in Simian Immunodeficiency Virus Isolates with Gag Epitope Cytotoxic T-Lymphocyte Escape Mutations

Abstract: The evolution of human immunodeficiency virus type 1 (HIV-1) and simian immunodeficiency virus (SIV) as they replicate in infected individuals reflects a balance between the pressure on the virus to mutate away from recognition by dominant epitope-specific cytotoxic T lymphocytes (CTL) and the structural constraints on the virus' ability to mutate. To gain a further understanding of the strategies employed by these viruses to maintain replication competency in the face of the intense selection pressure exerted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…Thus, a revised model of control is that HLA-B57 commonly selects a less fit viral variant containing T 242 N and that compensation for this capsid defect results in higher viremia and progressive disease. This model is consistent with the work of Gao et al (32), demonstrating that the protective effect of HLA-B57 occurs at early stages of disease and accumulating data indicating the importance of compensatory mutations coincident with or subsequent to CTL epitope escape (24,30,41,67). In addition to the potential for unknown compensatory mutations, control of HIV-1 likely is due to CTL pressure against multiple epitopes, which may be the case for HLA-B57 in particular, for which numerous CTL responses against Gag and other proteins have been described.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, a revised model of control is that HLA-B57 commonly selects a less fit viral variant containing T 242 N and that compensation for this capsid defect results in higher viremia and progressive disease. This model is consistent with the work of Gao et al (32), demonstrating that the protective effect of HLA-B57 occurs at early stages of disease and accumulating data indicating the importance of compensatory mutations coincident with or subsequent to CTL epitope escape (24,30,41,67). In addition to the potential for unknown compensatory mutations, control of HIV-1 likely is due to CTL pressure against multiple epitopes, which may be the case for HLA-B57 in particular, for which numerous CTL responses against Gag and other proteins have been described.…”
Section: Discussionsupporting
confidence: 92%
“…Two putative compensatory mutations have been associated with T 242 N, namely, a Gly-to-Ala (G 248 A) change at position 9 within the epitope and an upstream His-to-Gln (H 219 Q) mutation within the CypA-binding loop (44). Because viral escape may require multiple compensatory mutations (30,55,56,67), we first investigated whether additional sequence changes were associated with T 242 N by using data from studies by Migueles et al (49,50) that identified variations in Gag CTL epitopes in B57 Ď© individuals with progressive disease. Note that in contrast to plasma viral sequences obtained for the viremic individuals, data for subjects with an undetectable viral load (Ď˝50 copies/ ml) were derived from cellular proviral DNA using a limiting dilution technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many of those that do become selected are postulated to negatively affect virus fitness, as evidenced by rapid reversion to WT sequence when transmitted to hosts that lack the appropriate restriction element, or the requirement for co-selection of compensatory mutations that restore virus fitness (8,49,50). In a few cases, deleterious effects on virus fitness have been demonstrated directly in in vitro assays, using tissue culture cells or virus replicons (11,50,51). Consequently, a conclusion from these studies is that only a few mutations are selected because, despite their ability to evade CTL recognition, the vast majority negatively impact virus fitness.…”
Section: Discussionmentioning
confidence: 99%
“…These double mutants would take longer to arise than single beneficial mutants. Fitness interactions of this type, more generally known as fitness epistasis, are common and strong in HIV-1 in the context of its adaptation to an alternative host-cell coreceptor (Da Silva et al 2010) and have been reported for the evolution of escape mutants in response to CD8 + T cell selection (Yeh et al 2006;Schneidewind et al 2008).…”
Section: Discussionmentioning
confidence: 99%